Spotlight on the Granules (Grainyhead-Like Proteins) – From an Evolutionary Conserved Controller of Epithelial Trait to Pioneering the Chromatin Landscape - Sundararajan, Vignesh; Pang, Qing You; Choolani, Mahesh; Huang, Ruby Yun-Ju (Frontiers in Molecular Biosciences, 2020)
Among the transcription factors that are conserved across phylogeny, the grainyhead family holds vital roles in driving the epithelial cell fate. In Drosophila, the function of grainyhead (grh) gene is essential during developmental processes such as epithelial differentiation, tracheal tube formation, maintenance of wing and hair polarity, and epidermal barrier wound repair. Three main mammalian orthologues of grh: Grainyhead-like 1-3 (GRHL1, GRHL2, and GRHL3) are highly conserved in terms of their gene structures and functions. GRHL proteins are essentially associated with the development and maintenance of the epithelial phenotype across diverse physiological conditions such as epidermal differentiation and craniofacial development as well as pathological functions including hearing impairment and neural tube defects. More importantly, through direct chromatin binding and induction of epigenetic alterations, GRHL factors function as potent suppressors of oncogenic cellular dedifferentiation program – epithelial-mesenchymal transition and its associated tumor-promoting phenotypes such as tumor cell migration and invasion. On the contrary, GRHL factors also induce pro-tumorigenic effects such as increased migration and anchorage-independent growth in certain tumor types. Furthermore, investigations focusing on the epithelial-specific activation of grh and GRHL factors have revealed that these factors potentially act as a pioneer factor in establishing a cell-type/cell-state specific accessible chromatin landscape that is exclusive for epithelial gene transcription. In this review, we highlight the essential roles of grh and GRHL factors during embryogenesis and pathogenesis, with a special focus on its emerging pioneering function.